Penegakan Hukum Terhadap Pelanggaran Lalu Lintas Di Karawang - Dafa Ajaria Nurjaman; Intan Dwi Erianti; Bunga Annisa Salsabilla; Cindy Clara Pratiwi Sihombing; Syafa Aulina Prihartiwi; Dea Putri Novita (CV. ULIL ALBAB CORP, 2024)
Enforcement of traffic laws in Karawang has become a very important issue along with the increasing number of vehicles and traffic density. The aim of this research is to determine and analyze the effectiveness of traffic law enforcement in Karawang district, as well as identifying factors that influence the increasing number of traffic accidents in Karawang. There are several factors that influence the effectiveness of laws and regulations in Karawang regarding traffic, including a lack of public understanding of the laws, a lack of traffic facilities, and a driving culture of ignoring the rules and a lack of awareness of the law.